The Effect of Exposed Glass Fibers and Particles of Bioactive Glass on the Surface Wettability of Composite Implants - Aous A. Abdulmajeed; Lippo V. Lassila; Pekka K. Vallittu; Timo O. Närhi (International Journal of Biomaterials)
Measurement of the wettability of a material is a predictive index of cytocompatibility. This study was designed to evaluate the effect of exposed E-glass fibers and bioactive glass (BAG) particles on the surface wettability behavior of composite implants. Two different groups were investigated: (a) fiber reinforced composites (FRCs) with different fiber orientations and (b) polymer composites with different wt. % of BAG particles. Photopolymerized and heat postpolymerized composite substrates were made for both groups. The surface wettability, topography, and roughness were analyzed. Equilibrium contact angles were measured using the sessile drop method. Three liquids were used as a probe for surface free energy (SFE) calculations. SFE values were calculated from contact angles obtained on smooth surfaces. The surface with transverse distribution of fibers showed higher (𝑃<0.001) polar (𝛾P) and total SFE (𝛾TOT) components (16.9 and 51.04 mJ/m2, resp.) than the surface with in-plane distribution of fibers (13.77 and 48.27 mJ/m2, resp.). The increase in BAG particle wt. % increased the polar (𝛾P) value, while the dispersive (𝛾D) value decreased. Postpolymerization by heat treatment improved the SFE components on all the surfaces investigated (𝑃<0.001). Composites containing E-glass fibers and BAG particles are hydrophilic materials that show good wettability characteristics.